2021
DOI: 10.1108/jima-11-2020-0341
|View full text |Cite
|
Sign up to set email alerts
|

Key attributes of Muslim-friendly hotels’ service quality: voices from booking.com

Abstract: Purpose On a global scale, the Muslim-friendly hospitality business has intensified hotel competition. Given the paucity of research on the important service quality characteristics of Muslim-friendly hotels, this study aims to identify the major themes encountered by tourists at Muslim-friendly hotels. Design/methodology/approach The research used content analyzes (qualitative) to examine 1,250 reviews using Leximancer software. Data were gathered from the online travel website booking.com. The top 10 Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 95 publications
(167 reference statements)
8
72
0
Order By: Relevance
“…For example, Kim et al (2016) found that staff and their "attitude," "room cleanliness/dirtiness," "bed," "bathroom" and "room size" were identified as common satisfiers and dissatisfiers. While the work of Alrawadieh and Dincer (2019) study found that the most often hotel e-complaints included service quality, hotel facility efficiency, and cleanliness and hygiene, Arasli et al (2021) found that guests who score their hotel experiences as high satisfaction share narratives such as cleanliness, food, staff, hotel, restaurants, room and entertainment. Similarly, Arasli et al (2020b) researched cruise tourism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kim et al (2016) found that staff and their "attitude," "room cleanliness/dirtiness," "bed," "bathroom" and "room size" were identified as common satisfiers and dissatisfiers. While the work of Alrawadieh and Dincer (2019) study found that the most often hotel e-complaints included service quality, hotel facility efficiency, and cleanliness and hygiene, Arasli et al (2021) found that guests who score their hotel experiences as high satisfaction share narratives such as cleanliness, food, staff, hotel, restaurants, room and entertainment. Similarly, Arasli et al (2020b) researched cruise tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the widespread use of Web 2.0 technology in a wide range of fields, Web-based platforms may generate user-generated content (UGC) (Brochado et al , 2019). In addition, third-party agents, such as online reviews on Booking.com and Expedia (Arasli et al , 2021) and specific review portals such as Yelp and TripAdvisor, can generate UGC (Sulu et al , 2022). Consumers and decision-makers have benefited much from UGC analysis (Nilashi et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Through a three-part procedure [75], this type of map enables analysts to acquire insights into and comprehension of natural language (Figure 1). The software extracted semantic pattern information that enabled us to identify the key concepts and themes underlying passenger airline experiences in a concept map composed of concepts-represented by grey dots-that are then grouped into themes-represented by colored spheres [76]. The theme colors signify the significance of each theme, with themes heat-mapped from hottest to coolest (i.e., red-orange is the "hottest" or most noticeable theme, and purple is the "coolest" or least connected theme).…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al [4] collected data from Chinese travel blogs to research destination images. Another recent study done by Arasli et al [76] found key attributes of Muslim-friendly hotels' service quality using Leximancer. Brochado [79] researched nature-based experiences in tree houses focusing on guests' online reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation